97 Is improved heart failure mortality under cardiology because cardiologists are 'cherry-picking'?. (17th July 2020) - Latt, Nang Khaing Zar; Nemeth, Nora; Debski, Maciej; Faggioni, Alessandro; Taylor, Rebecca; Cassidy, Christopher; Seed, Alison; Wong, Suzanne; Wong, Kenneth
Abstract : Introduction: Heart Failure mortality is high -7% if patients are under the care of Cardiologists, or 11% if under general physicians (according to the national heart failure audit in 2013). It is unclear whether cardiologists are 'cherry-picking' patients who are less frail with fewer co-morbidities. Hypothesis and Aim: Cardiologists select patients who are less frail with fewer co-morbidities. We also aimed to compare the compliance to NICE quality standard and length of stay between patients admitted to general medical wards, cardiology ward in the Lancashire Cardiac Centre, and an Acute Cardiac Ward (ACW)-'Ward 19', led by Consultant Cardiologists, supported by a team of Cardiology juniors and nurses, adjacent to our Acute Medical Unit (AMU) in the District General Hospital (DGH) part of the Trust. Methodology: The study was carried out in Blackpool Victoria Hospital. The data was collected from 99 patients admitted to Blackpool Victoria Hospital. Data was collected retrospectively (random sample from 2016-8). Results: There is no significant difference in Derby Frailty Index between patients admitted to DGH wards, the ACW and Tertiary Cardiac Centre wards. The Rockwood frailty score was slightly higher in the DGH wards compared with the ACW, but not significantly different with the tertiary centre wards. More co-morbidities were observed in patients in the DGH wards compared with the ACW but not significantly different compared with the tertiary centre. However, there is no significant difference in the age of patients, or proportion of patient on palliative care. Importantly, the proportion of people who suffered 'falls'/ reduced mobility was not significantly different between the groups. Thus, our observation that more patients in Cardiology/ACW were receiving MRA could not be explained by lower blood pressure for instance. Limitations: There is significant difference in terms of heart failure treatment received in patients admitted under general medicine vs cardiology. However, tendency to falls in 1/3 of DGH patients may be a clinically important reason that may contribute to lower use of MRA in DGH (even though the small study has not found a statistically significant difference in % of patients who suffer falls). Notably, 13% DGH patients were discharged without echocardiography. Tendency for DGH wards to have higher frailty score, also multiple markers of frailty–incontinence, confusion, falls/reduced mobility (though not statistically significant) does suggest the cohort is more frail. Equally, they are probably appropriately placed for the MDT delivery of comprehensive geriatric assessment. The key is to ensure they receive cardiology/HF specialist input. Conclusion: We have found no definitive evidence to suggest Cardiologists are cherry-picking patients, in terms of age, creatinine, Derby Frailty index, falls, reduced mobility and palliative care. Patients in the ACW were slightly less frail (Rockwood score) with fewer comorbidities, but the proportion of patients who fall and BP is similar to DGH patients. Despite that, more Cardiology patients are on appropriate HF medication than DGH patients. More research is required to test whether it is possible to safely reduce the length of stay in patients in Cardiac wards and whether frail heart failure patients may cope with outpatient based therapy for acute decompensation. Conflict of Interest: No conflict of interest